Identificação e caracterização funcional de esfingomielinases salivares do carrapato Amblyomma sculptum - Paula Ferreira Franco (2019)
Amblyomma sculptum is a tick of medical and veterinary importance. In addition to being the main vector of Rickettsia rickettsii to humans and animals in Brazil, this species also causes great damage to livestock. During hematophagy, ticks secrete a large amount of saliva that has an arsenal of biologically active molecules which counteract the host's repair reactions and ensure success in blood ingestion. Among the salivary molecules of ticks, the sphingomyelinase D (SMasesD), which are enzymes capable of hydrolyzing sphingomyelin present in cell membranes, form the products ceramide 1-phosphate and choline. This enzyme was previously described in the venom of spiders of the genus Loxosceles sp. and are the major molecules involved in loxoscelism, causing severe cutaneous lesions such as dermonecrosis and other systemic effects such as intravascular hemolysis and platelet aggregation. In ticks, this enzyme was detected in the salivary transcripts of Rhipicephalus microplus, Amblyomma maculatum and Ixodes scapularis. The aim of this study was to verify the presence of this AsSMase D in the salivary gland (SG) of Amblyomma sculptum and to characterize its function. First, the presence of the enzyme was investigated in salivary gland extracts (SGEs) of tick females at diferent intervals post-feeding. It was possible to perceive the presence of activity and that it increases throughout hematophagy. Next, a search was made for sequences homologous to SMase D of the L. intermedia venom in a tick SG transcriptome. A 40% identity sequence was identified which possessed the amino acids responsible for the catalytic activity, characteristics of the SMases D. The protein, designated AsSMase D, was cloned into vector pET28a-TEV and expressed in Escherichia coli. The recombinant protein produced was called rAsSMase D, and through western blot analysis it was verified that anti-rAsSmaseD antibodies were able to recognize a native protein in females’ SGE. Through conventional PCR it was possible to detect the presence of AsSMase D mRNA at all stages of tick development (larvae, nymphs, males and females) and in SG of females. Analyzes using qPCR demonstrated that AsSMase D expression is higher in fasting female ticks and reduces gradually with the onset of blood supply, in agreement with the results obtained by the ELISA, which also demonstrated a decrease in the amount of proteins throughout hematophagy. By silencing the expression of the AsSMase D gene in the salivary gland of A. sculptum females through iRNA, about 90% reduction in the expression was observed. However, when using the silenced ticks in feeding trials in Swiss mice, it was not possible to notice a change in the feeding behavior of these ticks. A similar pattern was observed when evaluating the feeding of ticks in hosts immunized with rAsSMase D. In vivo and in vitro assays for the identification of protein function were performed. In order to evaluate the dermonecrotic capacity, New Zealand rabbits were injected with rAsSMase D, but no changes were observed. The ability of rAsSMase D to cause hemolysis in the alternative pathway hemolytic assay was also tested. It was possible to observe that rAsSMase D does not cause inhibition of hemolysis, but was able to cause a 17% increase in hemolysis process. The ability of rAsSMase D to activate the coagulation cascade and platelet aggregation was also evaluated, but only in the coagulation assay was it possible to detect a small increase in coagulation time. The results confirm the presence of a SMase D in the salivary gland of A. sculptum and indicate that the protein is found at higher levels at the beginning of feeding. New investigations will be performed in order to better elucidate the importance of AsSMase D in A. sculptum